Reputation, Transparency, Trust and Waqif's Perception on Nadzir’s Professional Toward Intention to Act Waqf: Empirical Study in Pondok Modern Darussalam Gontor (PMDG) - Azidni Rofiqo; Mohammad Muslih; Diyan Novita Sari (Muhammadiyah University Press, 2021)
This study aims to explore the reputation, transparency, trust, waqif perception of nadzir’s professionalism, and the intention to pay waqf in Gontor Institution. This study based on the theory of planned behavior (TPB) which examines the effect of reputation, transparency, trust toward waqif perception of Nadzir’s professionalism and intention to pay waqf. The approach this study is a quantitative approach with structural equation modeling-partial least square (SEM-PLS) measurements. The number of respondents 200 alumni of the Pondok Modern Darussalam Gontor. The findings in this study indicate that reputation, transparency, trust have a significant positive effect on the intention to pay waqf at Pondok Modern Darussalam Gontor with the waqif’s perception of nadzir’s professionalism as mediating effect. Other findings indicate that trust as moderating effect between reputation and waqif perception of nadzir’s professional.